2020
DOI: 10.1021/acssuschemeng.0c01661
|View full text |Cite
|
Sign up to set email alerts
|

Heteroatom-Doped Pillared Porous Carbon Architectures with Ultrafast Electron and Ion Transport Capabilities under High Mass Loadings for High-Rate Supercapacitors

Abstract: Retaining fast electron and ion transport of electrode materials at high mass loadings holds significant importance to supercapacitors. Carbon-based materials with ultrathin electrodes or small amounts of active materials on the current collectors, that is, active materials with a low mass loading (<1 mg cm–2), have achieved high capacitances and power densities with a fast charging/discharging rate. Yet, the low mass loading leads to low capacitances based on area or the device and, consequently, poor energy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…In the C 1s spectra of all electrolytes studied, the relative contents of compounds containing C−O bonds (284.5 eV) is low (Figure 3 a). [18] The graphite surface contains less organic components. It indicates that the decomposition of DME has not yet proceeded.…”
Section: Figurementioning
confidence: 99%
“…In the C 1s spectra of all electrolytes studied, the relative contents of compounds containing C−O bonds (284.5 eV) is low (Figure 3 a). [18] The graphite surface contains less organic components. It indicates that the decomposition of DME has not yet proceeded.…”
Section: Figurementioning
confidence: 99%
“…The Nyquist plots consist of a semicircle at the high‐medium frequency region and a sloping tail at the low frequency region (Figure S19a, Supporting Information), which are assigned to the charge‐transfer resistance ( R ct ) and Warburg impedance ( Z w ), respectively. [ 35 ] The kinetic parameters are well‐fitted according to the equivalent circuit (Figure S19b, Supporting Information). As shown in Figure 4e, MoS 2 /NG exhibits a R ct value of 91 Ω, two times lower than MoS 2 /G (187 Ω) due to the robust charge‐transfer kinetics enabled by the strong interfacial interaction (MoN bonds) between MoS 2 and N‐doped graphene.…”
Section: Resultsmentioning
confidence: 99%
“…The development of composites that combine pseudocapacitive behavior and EDLC response in highly porous structures (favored by high surface area and superior electrical conductivity) represents an important strategy to reach electrodes with outstanding electrochemical performance. Zhao et al [ 7 ] reported the development of high energy density and ultrahigh power density from the assembly of electrodes in the form of porous carbon pillars doped with heteroatoms.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatives to incorporate pseudocapacitance in highly porous carbon derivatives involve the self-doping and artificial doping processes in porous structures. Artificial doping is based on the post-treatment of thermally treated carbon with amines, urea, or phosphoric acid [ 7 ]. On the other hand, self-doping is based on direct carbonization/pyrolysis of specific biomass rich in groups that introduce a more homogeneous distribution of heteroatoms into the structure’s bulk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation